The Relationship between Quality of Health Care with BPJS Patient Satisfaction - Anggi Isnani Parinduri; Rahmad Khalid (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Hospitals are a health care institution that organizes multiple health services in a plenary, one of the important indicators that must be considered in health services is patient satisfaction. Patient satisfaction is one of the important elements in evaluating service quality by measuring the response of patients after receiving health care services. The patient satisfaction level also depends on the quality of services offered with patient expectations. This study aims to explain the relationship of the quality of health services with the satisfaction of BPJS participants. This research is a quantitative study with an analytic survey approach, using cross sectional design. The population in the study was all BPJS users in the inpatient room of the Grandmed Hospital Lubuk Pakam, the number of samples taken by 50 people with sampling techniques using purposive sampling. Data collection method using primary data and secondary data. Statistical test using chi square test with confidence level = 0.05. The results of the analysis showed that there was a relationship between patient satisfaction and reliability (p=0.016) and there was a relationship between patient satisfaction and responsiveness (p=0.001). It is hoped that the management, service department, health workers and all parties at Grandmed Lubuk Pakam Hospital to provide and improve services to patients in accordance with public service standards, because the services provided to patients show the quality of the hospital.